Edible Coating Techniques and Glycerol Concentration in Gels Aloe Vera (Aloe vera) on the Physical and Chemical Properties of Sweet Corn (Zea mays subsp. saccharata L.) - Rita Hayati; Marai Rahmawati; Isah Komariah (University of Prof. Dr. Hazairin, SH, 2023)
Respiration that occurs in sweet corn after harvest can cause the material to lose its substrate. With reduced respiration substrates, there is a loss of energy sources and a decrease in taste quality, so postharvest management must be carried out to slow down the rate of decline and extend the shelf life in corn, especially by using aloe vera gel and to optimize the quality of aloe vera gel it would be nice to add glycerol. This study used a factorial randomized block design (RBD). The two factors tested were the edible coating technique and the glycerol concentration. The results showed that the edible coating technique used in the form of dipping, spraying and basting had a very significant effect on moisture content, fat content, a (red) color, outer color, texture and overall acceptance and had a significant effect on aroma. Whereas the glycerol concentrations were 7%, 9% and 11% which significantly affected fat, a (red) color, outer color and overall acceptance. The best treatment was found in sweet corn with an edible coating spraying technique with a concentration of 7%. Keywords: aloe vera gel, glycerol, corn, respiration